Developmental changes in infant brain activity during naturalistic social experiences. Issue 7 (29th July 2015) - Jones, Emily J. H.; Venema, Kaitlin; Lowy, Rachel; Earl, Rachel K.; Webb, Sara Jane
ABSTRACT Between 6 and 12 months, typically developing infants undergo a socio‐cognitive "revolution." The Interactive Specialization (IS) theory of brain development predicts that these behavioral changes will be underpinned by developmental increases in the power and topographic extent of socially selective cortical responses. To test this hypothesis, we used EEG to examine developmental changes in cortical selectivity for ecologically valid dynamic social versus non‐social stimuli in a large cohort of 6‐ and 12‐month‐old infants. Consistent with the Interactive Specialization model, results showed that differences in EEG Θ activity between social and non‐social stimuli became more pronounced and widespread with age. Differences in EEG activity were most clearly elicited by a live naturalistic interaction, suggesting that measuring brain activity in ecologically valid contexts is central to mapping social brain development in infancy. © 2015 Wiley Periodicals, Inc. Dev Psychobiol 57: 842–853, 2015.